2006
DOI: 10.1017/s0001924000001536
|View full text |Cite
|
Sign up to set email alerts
|

Wing tip vortex control using synthetic jets

Abstract: An experimental investigation was conducted to study the effect of synthetic jet (oscillatory, zero net mass flow jet) blowing near the wing tip, as a means of diffusing the trailing vortex. Velocity measurements were taken, using a Particle Image Velocimetry system, around the tip and in the near wake of a rectangular wing, which was equipped with several blowing slots. The effect of the synthetic jet was compared to that of a continuous jet blowing from the same configurations. The results show that the use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…Intuitive control approaches of a tip vortex lead control engineers to actuate in the tip region of the control surface. Examples of this type of control use momentum injection through different configuration slots in the wing tip region (Margaris & Gursul 2006, 2010Edstrand & Cattafesta 2015). Alternative control strategies have modified the lift distribution through rapidly actuated miniature Gurney flaps along the trailing edge (Matalanis & Eaton 2007) and through trailing-edge blowing (Taira & Colonius 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Intuitive control approaches of a tip vortex lead control engineers to actuate in the tip region of the control surface. Examples of this type of control use momentum injection through different configuration slots in the wing tip region (Margaris & Gursul 2006, 2010Edstrand & Cattafesta 2015). Alternative control strategies have modified the lift distribution through rapidly actuated miniature Gurney flaps along the trailing edge (Matalanis & Eaton 2007) and through trailing-edge blowing (Taira & Colonius 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This could be useful in some applications as will be discussed later on. Turbulence ingestion into the developing tip vortex can be achieved for much lower momentum coefficients (on the order of 0.1%) with synthetic jets [55].…”
Section: B Control Of Tip Vortices Of High Aspect Ratio Wingsmentioning
confidence: 99%
“…These jet vortices have previously been generated through: a) blowing at an angle to the freestream direction; 11 b) self-generated jets (bleed) ejected perpendicular to the wing surface, where the pressure differential between the two wing surfaces provides the input energy; 12 and c) synthetic jets. 13 There is also evidence that far-wake interactions of co-rotating and counter-rotating vortex pairs can be affected by turbulence ingestion from blowing. [14][15][16] It has been theoretically shown that three-dimensional instabilities may grow in a counter-rotating vortex pair.…”
Section: Introductionmentioning
confidence: 99%